Investigation of Inhibition Effect on Pathogen Microorganisms by Adding NPAg to Activated Carbon Obtained by Activating Hazelnut Shell with ZnCl2 - Şükrü Karataş; Esra Altıntığ; Birsen Sarıcı (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi, 2025)
In this study, silver-coated activated carbon (NPAgAC) was obtained by adding nanoparticle silver (NPAg) to activated carbon (AC) produced from hazelnut shells by chemical activation and carbonization. SEM, FT-IR, and BET were evaluated. While the methylene blue (MB) number of the produced ACs was 490-499 mg/g, the MB numbers of NPAgAC were determined to be 421-453 mg/g. The iodine number of ACs was specified in the 1047-1612 mg/g range. The iodine numbers of NPAgACs were recorded in the 934-1022 mg/ g range. Additionally, EDS and XRD analyses were performed on all samples. Well, diffusion and spreading plate methods were used to control the antimicrobial properties of the produced NPAgAC. The study used Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) as pathogenic microorganisms. In addition, the antimicrobial properties of NPAgACs were investigated using the spread plate method at various times and temperatures to determine their effectiveness in inhibiting the growth of E. coli in polluted waters. Studies have shown that hazelnut shells are a suitable starting material for producing activated carbon, and that NPAgAC exhibits high antimicrobial properties with food safety.